Evaluation of Arabic Language Software Program - Ibrahim Sulimen Ahmed (2008)
CHAPTER 1 General Overview of Arabic Language SOftware Programs CHAPTER 2 The Role of the Language Teacher CHAPTER 3 Factors Affecting the Integration of Arabic CALL into the Arabic Curriculum CHAPTER 4 A Framework for the Educational Use of Internet Technologies and the Procedure of Evaluation CHAPETR 5 Literature Review CHAPTER 6 Evaluation of the "Lessons in Arabic Program" CHAPTER 7 Evaluation of the "Learn Arabic Program" CHAPTER 8 Evaluation of "Talk Now Program!" A General Overview CHAPTER 9 Evaluation of "Learn Arabic Program" CHAPTER 10 Evaluation of the Rosetta Stone (Arabic Explorer) CHAPTER 11 Evaluation of Learn Arabic Program CHAPTER 12 The Berlitz Passport to Arabic CHAPTER 13 An Analysis of the Arabic Language Program "The Wolf and the Seven Little Goats" CHAPTER 14 An Analysis of the Arabic Language Program for Beginners CHAPTER 15 AN Analysis of the Arabic Language Program "Learn Arabic 2" CHAPTER 16 Designing Arabic Language Software for Medical Students CHAPTER 17 Designing a Web Site for Computer Assisted Language Learning (Group) and Discussion Index